The role of iron and myelin in orientation dependent R2* of white matter. (30th April 2019) - Kor, Daniel; Birkl, Christoph; Ropele, Stefan; Doucette, Jonathan; Xu, Tianyou; Wiggermann, Vanessa; Hernández‐Torres, Enedino; Hametner, Simon; Rauscher, Alexander
Abstract : Brain myelin and iron content are important parameters in neurodegenerative diseases such as multiple sclerosis (MS). Both myelin and iron content influence the brain's R2 * relaxation rate. However, their quantification based on R2 * maps requires a realistic tissue model that can be fitted to the measured data. In structures with low myelin content, such as deep gray matter, R2 * shows a linear increase with increasing iron content. In white matter, R2 * is not only affected by iron and myelin but also by the orientation of the myelinated axons with respect to the external magnetic field. Here, we propose a numerical model which incorporates iron and myelin, as well as fibre orientation, to simulate R2 * decay in white matter. Applying our model to fibre orientation‐dependent in vivo R2 * data, we are able to determine a unique solution of myelin and iron content in global white matter. We determine an averaged myelin volume fraction of 16.02 ± 2.07% in non‐lesional white matter of patients with MS, 17.32 ± 2.20% in matched healthy controls, and 18.19 ± 2.98% in healthy siblings of patients with MS. Averaged iron content was 35.6 ± 8.9 mg/kg tissue in patients, 43.1 ± 8.3 mg/kg in controls, and 47.8 ± 8.2 mg/kg in siblings. All differences in iron content between groups were significant, while the difference in myelin content between MS patients and the siblings of MS patients was significant. In conclusion, we demonstrate that a model that combines myelin‐induced orientation‐dependent and iron‐induced orientation‐independent components is able to fit in vivo R2 * data. Abstract : A computational model, which incorporates iron content, myelin content, and fibre orientation to simulate R2 * decay in white matter, is proposed. Applying the model to fibre orientation dependent in vivo R2 * data, we were able to determine a unique solution of myelin and iron content in global white matter, with significantly increased iron content in healthy siblings of MS patients. We demonstrate that only a model combining myelin‐induced orientation‐dependent and iron‐induced orientation‐independent components is able to fit experimental R2 * data.